Video quality challenges in wireless networks - Sheraz, Maki Mohd Ahmed; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Abdullah, Tahani Abdullah; Yousif, Marwa Yousif (IJCSNS, 2014)
Wireless support is now available in most devices. Streaming video over networks is a big challenge that faced by most companies working in technology development. Giving the best quality and high throughput performance is an ongoing issue. The quality depends on many factors likes bound rates and stringency of the delay bounds and the characteristics of the wireless networks. Wireless networks are exposed to noise and interference and hence cause losses and delays. This paper aims to study the challenges of the video quality in wireless network.